Ruínas incômodas: sobrevivência e apagamento na obra Plasmatio de José Rufino - Januário , Lucian (2019)
In this research we analyze the work Plasmatio, by the artist José Rufino. The general objective was to analyze the main theoretical categories and concepts present in Plasmatio, since we start from the hypothesis that the artist works with more elements wich we use to experience time, not only memory, so that oblivion, erasure, missing‖ (saudade, in Portuguese) and anachronism are fundamental in the construction of this relationship. As a methodology, we applied the qualitative research, through the use of semi-structured interview, documentary analysis and bibliographical review, which besides being made on the production of José Rufino, also included the articulation with concepts such as hypermodernity of Gilles Lipovetsky, memory and forgetfulness in Andreas Huyssen and anachronism in Georges Didi-Huberman, we used the reflections on missing, an affection of great importance in Plasmatio, and the concept of capitalism as a religion in Walter Benjamin, as a means of understanding the sacrificial pathos that crosses the work and presents itself in the Shroud of Plasmatio.